Activation and regulation of endogenous retroviral genes in the human pituitary gland and related endocrine tumours - Buslei, R.; Strissel, Pamela; Henke, Christine; Schey, Regina; Lang, Nadine; Ruebner, M.; Stolt, Claus; Fabry, Ben; Buchfelder, Michael; Strick, Reiner (Neuropathology and Applied Neurobiology, 2015)
Adenohypophysis (AH) hormone-producing cells represent the origin of diverse groups of pituitary adenomas (PA). Deregulation of hypothalamic hormone receptors, growth factors and cAMP signalling have been implicated in the aetiology of PA. Endogenous retroviruses (ERVs) are derived from past exogenous retroviral infections and represent more than 8% of the human genome. Some ERV genes encode open reading frames and produce functional proteins, for example, the ERVW-1 envelope gene Syncytin-1, essential for placentogenesis, but also deregulated in human tumours. Data concerning ERV expression in the AH and related endocrine tumours are missing.Syncytin-1 protein was analysed in normal AH (n = 15) and compared with five PA subtypes (n = 117) by immunohistochemistry. Absolute gene expression of 20 ERV functional envelope genes and ERVW-5 gag was measured. PA tissues were examined for Syncytin-1 and the cAMP signalling marker phospho-CREB-Ser133 using immunohistochemistry. Isolated primary human PA cells were treated with different hormones. Murine embryonic and adult pituitary gland ERV expressions were compared with human AH.Syncytin-1 protein colocalized with corticotropic cells of AH. In contrast, all PA demonstrated significant Syncytin-1 protein overexpression, supporting deregulation. All other ERV genes showed significant up-regulations in different PA subtypes. Phospho-CREB-Ser133 and Syncytin-1 colocalized in PA cells. Cultivated primary PA cells with ACTH or CRH induced their respective receptors and ERV genes. Syncytin-A/-B, murine orthologues to human Syncytin-1/-2, localized to embryonic and adult pituitary glands demonstrating functional mammalian conservation.Deregulated ERV genes may contribute to PA development via cAMP signalling.
EVALuna2:4955

Inhibiting DNA Methylation Causes an Interferon Response in Cancer via dsRNA Including Endogenous Retroviruses - Chiappinelli, Katherine B.; Strissel, Pamela; Desrichard, Alexis; Li, Huili; Henke, Christine; Akman, Benjamin; Hein, Alexander; Rote, Neal S.; Cope, Leslie M.; Snyder, Alexandra; Makarov, Vladimir; Buhu, Sadna; et al. (Cell, 2015)
We show that DNA methyltransferase inhibitors (DNMTis) upregulate immune signaling in cancer through the viral defense pathway. In ovarian cancer (OC), DNMTis trigger cytosolic sensing of double-stranded RNA (dsRNA) causing a type I interferon response and apoptosis. Knocking down dsRNA sensors TLR3 and MAVS reduces this response 2-fold and blocking interferon beta or its receptor abrogates it. Upregulation of hypermethylated endogenous retrovirus (ERV) genes accompanies the response and ERV overexpression activates the response. Basal levels of ERV and viral defense gene expression significantly correlate in primary OC and the latter signature separates primary samples for multiple tumor types from The Cancer Genome Atlas into low versus high expression groups. In melanoma patients treated with an immune checkpoint therapy, high viral defense signature expression in tumors significantly associates with durable clinical response and DNMTi treatment sensitizes to anti-CTLA4 therapy in a pre-clinical melanoma model.
EVALuna2:17550

Long-Term Endurance Exercise in Humans Stimulates Cell Fusion of Myoblasts along with Fusogenic Endogenous Retroviral Genes In Vivo - Frese, Sebastian; Rübner, Matthias; Suhr, Frank; Konou, Thierry M.; Tappe, Kim A.; Toigo, Marco; Jung, Hans H.; Henke, Christine; Steigleder, Ruth; Strissel, Pamela; Hübner, Hanna; Beckmann, Matthias; et al. (PLoS ONE, 2015)
Myogenesis is defined as growth, differentiation and repair of muscles where cell fusion of myoblasts to multinucleated myofibers is one major characteristic. Other cell fusion events in humans are found with bone resorbing osteoclasts and placental syncytiotrophoblasts. No unifying gene regulation for natural cell fusions has been found. We analyzed skeletal muscle biopsies of competitive cyclists for muscle-specific attributes and expression of human endogenous retrovirus (ERV) envelope genes due to their involvement in cell fusion of osteoclasts and syncytiotrophoblasts. Comparing muscle biopsies from post- with the pre-competitive seasons a significant 2.25-fold increase of myonuclei/mm fiber, a 2.38-fold decrease of fiber area/nucleus and a 3.1-fold decrease of satellite cells (SCs) occurred. We propose that during the pre-competitive season SC proliferation occurred following with increased cell fusion during the competitive season. Expression of twenty-two envelope genes of muscle biopsies demonstrated a significant increase of putative muscle-cell fusogenic genes Syncytin-1 and Syncytin-3, but also for the non-fusogenic erv3. Immunohistochemistry analyses showed that Syncytin-1 mainly localized to the sarcolemma of myofibers positive for myosin heavy-chain isotypes. Cellular receptors SLC1A4 and SLC1A5 of Syncytin-1 showed significant decrease of expression in post-competitive muscles compared with the pre-competitive season, but only SLC1A4 protein expression localized throughout the myofiber. Erv3 protein was strongly expressed throughout the myofiber, whereas envK1-7 localized to SC nuclei and myonuclei. Syncytin-1 transcription factors, PPAR? and RXR?, showed no protein expression in the myofiber, whereas the pCREB-Ser133 activator of Syncytin-1 was enriched to SC nuclei and myonuclei. Syncytin-1, Syncytin-3, SLC1A4 and PAX7 gene regulations along with MyoD1 and myogenin were verified during proliferating or actively-fusing human primary myoblast cell cultures, resembling muscle biopsies of cyclists. Myoblast treatment with anti-Synycytin-1 abrogated cell fusion in vitro. Our findings support functional roles for ERV envelope proteins, especially Syncytin-1, contributing to cell fusion of myotubes.
EVALuna2:17549

Regulation of murine placentogenesis by the retroviral genes Syncytin-A, Syncytin-B and Peg10 - Henke, Christine; Ruebner, Matthias; Faschingbauer, Florian; Stolt, Claus; Schäfer, Natascha; Lang, Nadine; Beckmann, Matthias; Strissel, Pamela; Strick, Reiner (Differentiation, 2013)
The murine placenta has a trichorial structure with two multinucleated syncytiotrophoblast (SCT) layers representing a barrier between the maternal and fetal blood system. Genes of endogenous retroviruses and retrotransposon-derived paternally expressed genes (Peg), remnants of past infections and integrations in the genome, have essential functions in placentogenesis. Previous studies showed that the envelope genes Syncytin-A and Syncytin-B were essential for cell-cell fusion of the SCT. The goal of this study was to analyze the temporal localization and expression of nine genes throughout placental development from embryonic day (E)8.5 to E18.5 using in situ-hybridization and absolute RNA-quantification. These included a comparison of previously characterized genes from the labyrinth Syncytin-A, Syncytin-B, Gcm1, the junctional zone PL-1, PL-2, Plf, Tpbpa with two further characterized genes Peg10 and Tpbpb. Syncytin-A and Syncytin-B RNA localized to SCT-I and SCT-II, respectively. Peg10 RNA localized to all extraembryonic tissues, specifically to the parietal and sinusoidal TGC of the labyrinth layer, which is in contact with SCT-I and the maternal blood. All three retroviral/retrotransposon-derived genes showed the highest expression at E16.5, but Peg10 with 188,917.1 molecules/ng cDNA was 208-fold and 106.8-fold higher expressed than Syncytin-A and Syncytin-B, respectively. Tpbpb localized to the junctional zone and showed the highest expression at E16.5 along with PL-2, Plf, Tpbpa, but not PL-1, which decreased in expression at E10.5. To investigate a role of Syncytin-A, Syncytin-B and Peg10 in cell-cell fusion, we established a cell culture system with fractionated primary trophoblasts from murine placentae. Culturing trophoblasts for up to 72h partly resembled trophoblast development in vivo according to the nine marker genes. Knockdown of Syncytin-A demonstrated a functional regulation of cell-cell fusion, where knockdown of Peg10 showed no involvement in cell fusion. Due to the expression of Peg10 in TGCs, we propose an essential functional role in the fetal-maternal blood system.
EVALuna2:4934

Selective expression of sense and antisense transcripts of the sushi-ichi-related retrotransposon - derived family during mouse placentogenesis - Henke, Christine; Strissel, Pamela; Schubert, Maria-Theresa; Mitchell, Megan; Stolt, Claus; Faschingbauer, Florian; Beckmann, Matthias; Strick, Reiner (Retrovirology, 2015)
LTR-retrotransposons became functional neogenes through evolution by acquiring promoter sequences, regulatory elements and sequence modification. Mammalian retrotransposon transcripts (Mart1-9), also called sushi-ichi-related retrotransposon-homolog (SIRH) genes, are a class of Ty3/gypsy LTR-retroelements showing moderate homology to the sushi-ichi LTR-retrotransposon in pufferfish. Rtl1/Mart1 and Peg10/Mart2 expression in mouse placenta and demonstration of their functional roles during placental development exemplifies their importance in cellular processes. In this study, we analyzed all eleven mouse Mart genes from the blastocyst stage and throughout placentogenesis in order to gain information about their expression and regulation.Quantitative PCR, in situ hybridization (ISH) and immunoblotting showed various expression patterns of the 11 mouse Mart genes through different placental stages. Zcchc5/Mart3, Zcchc16/ Mart4 and Rgag1/Mart9 expression was undetectable. Rtl1/Mart1, Peg10/Mart2, Rgag4/Mart5 - Cxx1a,b,c/Mart8b,c,a gene expression was very low at the blastocyst stage. Later placental stages showed an increase of expression for Rtl1/Mart1, Rgag4/Mart5 - Cxx1a,b,c/Mart8b,c,a, the latter up to 1,489 molecules/ng cDNA at E9.5. From our recently published findings Peg10/Mart2 was the most highly expressed Mart gene. ISH demonstrated sense and antisense transcript co-localization of Rgag4/Mart5 to Cxx1a,b,c/Mart8b,c,a in trophoblast subtypes at the junctional zone, with an accumulation of antisense transcripts in the nuclei. To validate these results, we developed a TAG-aided sense/antisense transcript detection (TASA-TD) method, which verified sense and antisense transcripts for Rtl1/Mart1, Rgag4/Mart5 - Cxx1a,b,c/Mart8b,c,a. Except for Rtl1/Mart1 and Cxx1a,b/Mart8b,c all other Mart genes showed a reduced amount of antisense transcripts. Northern blot and 5' and 3' RACE confirmed both sense and antisense transcripts for Ldoc1/Mart7 and Cxx1a,b,c/Mart8b,c,a. Immunoblotting demonstrated a single protein throughout all placental stages for Ldoc1/Mart7, but for Cxx1a,b,c/Mart8b,c,a a switch occurred from a 57 kDa protein at E10.5 and E14.5 to a 25 kDa protein at E16.5 and E18.5.RNA and protein detection of mouse Mart genes support neo-functionalization of retrotransposons in mammalian genomes. Undetectable expression of Zcchc5/Mart3, Zcchc16/Mart4 and Rgag1/Mart9 indicate no role during mouse placentogenesis. Rgag4/Mart5 to Cxx1a,b,c/Mart8b,c,a gene expression support a role for differentiation from the ectoplacental cone. Mart antisense transcripts and protein alterations predict unique and complex molecular regulation in a time directed manner throughout mouse placentogenesis.
EVALuna2:4979

Surprising prenatal toxicity of epidermal lipoxygenase-3 - Vierling, F.; Dick, Angela; Wahlbuhl, Mandy; Krieg, P.; Henke, Christine; Ruebner, M.; Schneider, Holm (Placenta, 2014)
Metabolites of the epidermal lipoxygenase-3 (eLOX-3) are involved in various metabolic pathways. Most unexpectedly, intra-amniotic delivery of eLOX-3 to mice at gestational day 14.5, both via an adenoviral vector and as recombinant protein, resulted in fetal growth restriction and intrauterine death. Periodic acid-Schiff staining and RT-PCR analysis of placentae from fetuses exposed to eLOX-3 indicated a lack of glycogen trophoblasts in the junctional zone. Placenta-specific gene expression was altered. Thus, the observed prenatal toxicity of eLOX-3 could be due to a strong effect on placental development.
EVALuna2:17431